Cross-talk between engineered Clostridium acetobutylicum and Clostridium ljungdahlii in syntrophic cocultures enhances isopropanol and butanol production - Otten, Jonathan K.; Hill, John D.; Willis, Noah B.; Dougherty, Joseph; Dalton, Andrew; Papoutsakis, Eleftherios T. (Frontiers in Microbiology, 2025)
There is a need for efficient and sustainable production of essential chemicals such as isopropanol and butanol from renewable sugar feedstocks. Microbial fermentations use glycolysis, and as result, a third of the sugar carbon is lost to CO2 through pyruvate decarboxylation to acetyl-CoA, the starting intermediate for the biosynthesis of most microbial metabolites. In nature, microbes exist in syntrophic consortia, allowing for mutually-beneficial interactions, the production of novel products, and the realization of novel benefits—including better carbon conservation—not seen in monocultures. We examined the impact of starting coculture cell densities, the gas atmosphere (N2, H2, or H2/CO2) and coculture species ratios (using a recently developed RNA-FISH flow cytometric assays) on metabolite production, yields and sugar-carbon utilization in serum bottles and bioreactors. Metabolic flux analysis identified the complex patterns by which the two species alter each other’s metabolism in a cell-density and gas-atmosphere dependent manner. For increased acetone production, we transformed Clostridium acetobutylicum with a plasmid (p95ace02a) expressing a synthetic acetone pathway comprising four native genes. This engineered C. acetobutylicum was cocultured with Clostridium ljungdahlii to capture the waste CO2 and H2 generated due to glucose catabolism by C. acetobutylicum, and to convert acetone into isopropanol. C. ljungdahlii activated the dormant acetate uptake in C. acetobutylicum, while coculture density dramatically impacted species ratios, electron management, and the H2 utilization of C. ljungdahlii. We achieved exceptionally-high concentrations of our desired products—246 mM isopropanol and 148 mM butanol—in 64 h, with about 85% of the production occurring before 32 h. We reached maximum productivities of 13.9 mM isopropanol/h and 10.4 mM butanol/h with 0.9 mol alcohol produced per mol of sugar consumed. Total product yields reached 84.7% on a C-mol basis, versus 65.6% that can be reached in a C. acetobutylicum monoculture. Engineered syntrophic cocultures can efficiently and tunably produce target chemicals including isopropanol and butanol for a renewable economy.